Bioinspired Actuators Based on Stimuli‐Responsive Polymers. Issue 14 (9th May 2019) - Cui, Huanqing; Zhao, Qilong; Wang, Yunlong; Du, Xuemin
Abstract: Organisms exhibit strong environmental adaptability by controllably adjusting their morphologies or fast locomotion; thus providing constant inspiration for scientists to develop artificial actuators that not only have diverse and sophisticated shape‐morphing capabilities, but can also further transfer dynamic and reversible shape deformations into macroscopic motion under the following principles: asymmetric friction, the Marangoni effect, and counteracting forces of the surrounding conditions. Among numerous available materials for fabricating bioinspired artificial actuators, stimuli‐responsive polymers are superior in their flexible features and the ability to change their physicochemical properties dynamically under external stimuli, such as temperature, pH, light, and ionic strength. Herein, different mechanisms, working principles, and applications of stimuli‐responsive polymeric actuators are comprehensively introduced. Furthermore, perspectives on existing challenges and future directions of this field are provided. Abstract : Mimicking movement : Nature offers numerous examples of environmental adaptability by controllably adjusting the morphologies or fast locomotion of organisms; thus providing inspiration for artificial actuators that have diverse and sophisticated shape‐morphing capabilities, and transfer the dynamic and reversible shape deformations into macroscopic motion. Herein, different mechanisms, working principles, and applications of bioinspired stimuli‐responsive polymeric actuators are reviewed.